2022
DOI: 10.1111/cge.14185
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the relationship between familial dysbetalipoproteinemia and genetic variants in theAPOEgene

Abstract: Familial Dysbetalipoproteinemia (FD) is the second most common monogenic dyslipidemia and is associated with a very high cardiovascular risk due to cholesterolenriched remnant lipoproteins. FD is usually caused by a recessively inherited variant in the APOE gene (ε2ε2), but variants with dominant inheritance have also been described. The typical dysbetalipoproteinemia phenotype has a delayed onset and requires a metabolic hit. Therefore, the diagnosis of FD should be made by demonstrating both the genotype and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
13
0
1
Order By: Relevance
“…The assignment of pathogenicity of rare gene variants is an important medical problem nowadays. 33 LDLR gene-specific software improves predicting capacity for assessing the pathogenicity of LDLR variants in FH. 34 Given the large number of APOE genetic variants described so far, 11 and probably more in the next future, the implementation of such a tool would constitute a valuable approach to help to solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…The assignment of pathogenicity of rare gene variants is an important medical problem nowadays. 33 LDLR gene-specific software improves predicting capacity for assessing the pathogenicity of LDLR variants in FH. 34 Given the large number of APOE genetic variants described so far, 11 and probably more in the next future, the implementation of such a tool would constitute a valuable approach to help to solve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of five hyper responders with T2D or prediabetes on VLCKD noted one patient with a APOE E2/E2 genotype, and three with a high burden of genetic polymorphisms [26 ▪ ]. Monogenetic causes include familial hypercholesterolaemia, elevated lipoprotein (a) (Lp(a)), and familial dysbetalipoproteinaemia with variations in ApoE, particularly E2/E2 [32 ▪ ,33 ▪ ]. Heterozygous familial hypercholesterolaemia affects 1 in 250 people, and homozygous familial hypercholesterolaemia occurs in 1 in 300 000 people; however, despite being easily diagnosed and treated, only 10% of patients are thought to be diagnosed, with many unidentified and at risk [32 ▪ ].…”
Section: Dyslipidaemia and Cardiovascular Riskmentioning
confidence: 99%
“…FD has not only an autosomal recessive but also an autosomal dominant form. Approximately 30 APOE variants associated with the autosomal dominant FD have been previously reported [13][14][15]. However, the assessment of the pathogenicity of these variants has either not been previously carried out or has not been presented in full.…”
Section: Apoe Variants Associated With the Autosomal Dominant Fdmentioning
confidence: 99%
“…It was also shown that around 10% of patients could have the autosomal dominant FD associated with a single copy of the defective APOE allele. Approximately 30 APOE variants associated with the autosomal dominant FD have been reported [13][14][15]. However, there are insufficient data regarding the relationship between the described APOE variants and FD [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation